Kontektualisasi Visi Pendidikan Al-Qur'an Dalam Lembaga Pendidikan Kontemporer - Arif Arif; Wedra Aprison (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
The education of the Quran plays a key role in shaping the character, morality, and spirituality of individual Muslims. The vision of Quranic education extends beyond the mere understanding of the text, encompassing the introduction and application of Islamic values in everyday life. Contextualizing the vision of Quranic education involves an effort to comprehend and apply the teachings of the Quran in varying contexts of time and place. This article explores how the vision of Quranic education can be integrated and developed within educational institutions through a qualitative descriptive approach and literature review. The findings indicate that Quranic education involves not only understanding the text, but also the practice of Islamic ethics, the cultivation of noble virtues, the teaching of Arabic language, exegesis, hadith, and the study of the historical and cultural context in which the Quran was revealed. The integration of Quranic teachings into educational curricula, interactive teaching methods, character development, and the promotion of social awareness and inclusive education are crucial strategies in implementing the vision of Quranic education within educational institutions. Through these measures, Quranic education can shape a generation of Muslims with strong religious knowledge, virtuous character, and the ability to contribute positively to society as a whole.